2006
DOI: 10.1097/01.tp.0000199318.17013.c5
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study Investigating the Cost Effectiveness of Intraoperative Blood Salvage during Liver Transplantation

Abstract: Intraoperative red blood cell salvage and autologous transfusion is cost effective in adult liver transplantation. Currently, where optimum resource utilization and fiscal constraint are paramount in healthcare delivery, autologous transfusion is an important adjunct in liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…It has been reported that the levels of 2,3-DPG and ATP in recovered RBCs was higher than that in stored RBCs (22). In addition, it has been demonstrated that recovered blood cells exhibited an improved oxygen carrying capacity and stronger anti-infiltration capacity than stored blood cells, which reduce the incidence of metabolic acidosis and electrolyte imbalance caused by the infusion of a large number of stored blood cells (23). Other studies that compared intraoperative cell salvage with allogeneic blood transfusion have demonstrated an increased mean erythrocyte viability, increased 2,3-DPG (24,25) and increased ATP levels (26,27) in salvaged blood.…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported that the levels of 2,3-DPG and ATP in recovered RBCs was higher than that in stored RBCs (22). In addition, it has been demonstrated that recovered blood cells exhibited an improved oxygen carrying capacity and stronger anti-infiltration capacity than stored blood cells, which reduce the incidence of metabolic acidosis and electrolyte imbalance caused by the infusion of a large number of stored blood cells (23). Other studies that compared intraoperative cell salvage with allogeneic blood transfusion have demonstrated an increased mean erythrocyte viability, increased 2,3-DPG (24,25) and increased ATP levels (26,27) in salvaged blood.…”
Section: Discussionmentioning
confidence: 96%
“…3,4 Liver transplant is associated with major use of allogeneic blood products, which places major demands on finite resources and increases recipient exposure to viral, bacterial, and protozoal diseases associated with transfusion-undesirable events in immunosuppressed patients. 1 During this procedure, abnormal bleeding typically occurs as a consequence of surgery, hemostatic dysfunction, and portal hypertension. The cause of abnormalities of hemostasis is multifactorial, including deficits in platelets and coagulation factors related to the existing liver disease and increased fibrinolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, 40% operations are performed without blood transfusion. 1,2 During liver transplant, there is a major amount of blood loss because of surgery and primary disease. By using a cell saver, the need for blood transfusion is markedly reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of t-PA clearance during the anhepatic phase allied to the burst release of t-PA associated with the reperfusion of the ischemic graft result in great amounts of circulating tissue-type plasminogen activator (t-PA), with the consequent pathological activation of the fibrinolytic system 3 . Intraoperative red blood cell salvage (IRCBS) and autologous transfusion is not routinely used as cost effectiveness is a major concern 1 . The aim of this study was to analyse the changes in the transfusion requirements with the routine use of intraoperative red blood cell salvage.…”
Section: Introductionmentioning
confidence: 99%
“…Liver transplantation is associated with significant use of allogenic blood products, which places considerable demands on finite resources and increases recipient exposure to viral, bacterial and protozoal diseases associated with transfusion, undesirable events in immunosuppressed patients 1 . Intraoperative bleeding and homologous transfusions, during liver transplantation, are associated with increased postoperative morbidity and mortality in the recepients 2 .…”
Section: Introductionmentioning
confidence: 99%